Quorum Sensing Interference and Structural Variation of Quorum Sensing Mimics in Australian Soft Coral - Freckelton, Marnie L.; Høj, Lone; Bowden, Bruce F. (Frontiers in Marine Science, 2018)
Bacterial Quorum Sensing (QS), the indirect regulation of gene expression through production and detection of small diffusible molecules, has emerged as a point of interaction between eukaryotic host organisms and their associated microbial communities. The extracellular nature of QS molecules enables interference in QS systems, in many cases via mimicry. This study targeted QS induction and inhibition in soft coral holobionts, as many soft coral species commonly contain compounds with structural similarities to the well-studied bacterial QS molecules acyl homoserine lactones. Screening with two bacterial biosensors, Agrobacterium tumefaciens A136 and Chromobacterium violaceum CV026, demonstrated that QS interference differed between the two biosensor strains and extended across the soft coral families Alcyoniidae, Clavulariidae, Nephtheidae, and Xeniidae. Bioassay-guided fractionation revealed chemical activity patterns, particularly in the induction of QS. Cembranoid diterpenes from active fractions were purified and tested for QS interference activity. Interestingly, the type of QS activity (induction or inhibition) in A. tumefaciens A136 correlated with structural variability of the secondary oxygen ring; cembranoid diterpenes with a furan ring or five-membered lactone induced QS, while compounds with larger (six or seven membered) lactone rings inhibited QS. Addition of the dominant cembranoid diterpene in the soft coral Lobophytum compactum, isolobophytolide, to bacterial culture media increased the number and morphological diversity of bacteria recovered from the mucosal layer of this soft coral, demonstrating a selective effect on certain members of the soft coral bacterial community. The identity and QS activity of recovered isolates differed between the mucosal layers of L. compactum and Sinularia flexibilis. In conclusion, this study provides information on the complexity of the interaction between soft corals and their associated bacteria, as well as, a structural understanding of how QS mimic compounds are able to interfere with a bacterial communication system.